Nghiên cứu thiết kế chế tạo máy đo xa Laser rắn bước sóng 1,54 tần lặp cao - Hồ, Quang Quý (2011)
Tác giả: Hồ Quang Quý, PGS,TS; Phạm Vũ Thịnh, TS; Trần Thế Anh, ThS; Lê Thanh Hải, ThS -- Từ khóa: Máy đo xa; Máy đo lade